The herpes simplex virus 1-encoded envelope glycoprotein B activates NF-κB through the Toll-like receptor 2 and MyD88/TRAF6-dependent signaling pathway. - Mingsheng Cai (PLoS ONE, 2013)
The innate immune response plays a critical role in the host defense against invading pathogens, and TLR2, a member of the Toll-like receptor (TLR) family, has been implicated in the immune response and initiation of inflammatory cytokine secretion against several human viruses. Previous studies have demonstrated that infectious and ultraviolet-inactivated herpes simplex virus 1 (HSV-1) virions lead to the activation of nuclear factor kappa B (NF-κB) and secretion of proinflammatory cytokines via TLR2. However, except for the envelope glycoprotein gH and gL, whether there are other determinants of HSV-1 responsible for TLR2 mediated biological effects is not known yet. Here, we demonstrated that the HSV-1-encoded envelope glycoprotein gB displays as molecular target recognized by TLR2. gB coimmunoprecipitated with TLR2, TLR1 and TLR6 in transfected and infected human embryonic kidney (HEK) 293T cells. Treatment of TLR2-transfected HEK293T (HEK293T-TLR2) cells with purified gB results in the activation of NF-κB reporter, and this activation requires the recruitment of the adaptor molecules myeloid differentiation primary-response protein 88 (MyD88) and tumor necrosis factor receptor-associated factor 6 (TRAF6) but not CD14. Furthermore, activation of NF-κB was abrogated by anti-gB and anti-TLR2 blocking antibodies. In addition, the expression of interleukin-8 induced by gB was abrogated by the treatment of the human monocytic cell line THP-1 with anti-TLR2 blocking antibody or by the incubation of gB with anti-gB antibody. Taken together, these results indicate the importance and potency of HSV-1 gB as one of pathogen-associated molecular patterns (PAMPs) molecule recognized by TLR2 with immediate kinetics.